2011
DOI: 10.1657/1938-4246-43.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Expanded and Recently Increased Glacier Surging in the Karakoram

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
231
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(245 citation statements)
references
References 50 publications
12
231
2
Order By: Relevance
“…This may be a result of the location, which is closer to Issyk-Kul Basin, where moist air masses originating from the large lake penetrate through the Terskey Alatau Range (Dikikh et al 1991). The advancing and surging of glaciers has been described for the Karakorum (Copland et al 2011) and the Pamir (Kotlyakov et al 2008), as well as some Tien Shan ranges (Dolgushin and Osipova 1975, Narama et al 2010, Pieczonka et al 2013; and is now reported for the first time for the 'SJRB'. Surprisingly, the largest glacier, No.…”
Section: Glacier Changesmentioning
confidence: 86%
“…This may be a result of the location, which is closer to Issyk-Kul Basin, where moist air masses originating from the large lake penetrate through the Terskey Alatau Range (Dikikh et al 1991). The advancing and surging of glaciers has been described for the Karakorum (Copland et al 2011) and the Pamir (Kotlyakov et al 2008), as well as some Tien Shan ranges (Dolgushin and Osipova 1975, Narama et al 2010, Pieczonka et al 2013; and is now reported for the first time for the 'SJRB'. Surprisingly, the largest glacier, No.…”
Section: Glacier Changesmentioning
confidence: 86%
“…This glacial growth appears to be driven "by a quirk of the atmospheric general circulation that is not understood"; "more snow is being delivered to the mountain range at present, and less heat" (Cogley, 2012). Gardelle et al (2012) have provided strong evidence for the existence of an increasing ice mass balance in the Karakoram region, and Copland et al (2011) stress that contrary to what is often claimed about many of Earth's mountain glaciers, "it is evident that glacier surging is more extensive than previously reported in the Karakoram and that the number of glacier surges has increased recently," driven by positive mass balances.…”
Section: Discussionmentioning
confidence: 99%
“…• Copland et al (2011) used a combination of previously published literature and repeat satellite imagery to catalog ice behavior in the Karakoram since 1961. They found "there has been a marked increase in the recent occurrence of glacier surging in the Karakoram" associated with "a significant increase in winter, summer, and annual precipitation in the Karakoram over the period ."…”
Section: Other Researchmentioning
confidence: 99%
“…The glacier mass balance budget in the Karakoram positively affected the 2003-08 specific mass balance for the entire HKH region, which was estimated by Kääb et al (2012) into 20.21 6 0.05 m yr 21 of water equivalent. In particular, some studies discuss the expansion and thickening of the largest glaciers, mainly in the central Karakoram, since the 1990s, accompanied by a nonnegligible number of rapid glacier advances (i.e., surge-type phenomena; see, e.g., Diolaiuti et al 2003;Hewitt 2005;Barrand and Murray 2006;Mayer et al 2011;Copland et al 2011;Minora et al 2013).…”
Section: Introductionmentioning
confidence: 99%